Interventional cardiology in the elderly, at the time of TAVI and left atrial appendage occlusion - Pépin, Marion; Hauguel-Moreau, Marie; Grognet, Alix; Decaix, Théodore (Soins. Gérontologie, 2021)
Interventional cardiology is increasingly being offered to frail elderly people thanks to significant technical progress. Transcatheter aortic valve implantation allows the treatment of aortic stenosis by implanting an aortic bioprosthesis through a catheter, without surgery. The left atrial appendage occlusion limits the risk of ischemic stroke in patients with atrial fibrillation who have a contraindication to anticoagulants. These procedures remain invasive and must be proposed after multidisciplinary consultation.